Measuring Theory of Mind in Adults with Autism Spectrum Disorder - Brewer, Neil (J Autism Dev Disord, 2017)
Deficits in Theory of Mind (ToM)—the ability to interpret others’ beliefs, intentions and emotions—undermine the ability of individuals with Autism Spectrum Disorder (ASD) to interact in socially normative ways. This study provides psychometric data for the Adult-Theory of Mind (A-ToM) measure using video-scenarios based in part on Happé’s (Instructions for theory of mind story task, 1999) Strange Stories test. The final items discriminated IQ-matched adults with ASD from controls on the social but not the physical items. Additional validity data included a two-component principal components solution, correlations with existing ToM scales, and the absence of correlations with self-report measures of empathy and social anxiety (not requiring inferences about the intent of others). The expected group differences in ToM were accompanied by marked variability in the ASD sample. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s10803-017-3080-x) contains supplementary material, which is available to authorized users.